American, British and European recommendations for statins in the primary prevention of cardiovascular disease applied to British men studied prospectively. Issue 9 (22nd May 2006) - Mcelduff, P; Jaefarnezhad, M; Durrington, P N
Abstract : Objective: To compare national and international recommendations for statin treatment in the primary prevention of cardiovascular disease (CVD) in middle-aged men. Design: Application of the current American, British and European recommendations to results of a prospective study. Participants: Men aged 49–65 years (n  =  1653) who participated in the Caerphilly Prospective Study. Main outcome measures: Proportion of patients who would receive statin treatment, the number needed to treat (NNT) to prevent one first CVD event (myocardial infarction or stroke) over 10 years and the potential number of events prevented over 10 years in the whole population (population impact) by the use of statins in accordance with each set of guidelines, assuming a reduction of risk in the range 10–50% from the observed events and baseline risk factors. Results: 212 events were noted. For an anticipated reduction in first CVD events of 30% with statin treatment, the NNT was 26.0, if the whole population was treated. The lowest NNT was 12.1 for the National Service Framework, achieved when only 14% of the men received a statin. This prevented the lowest number of events (19.2/212), however, and had the smallest population impact on CVD incidence (−9.1%). The American and earlier Joint British Societies guidelines, although giving NNTs of around 21, prevented more events and had a greater population impact of −21.6% to −23.3%. They did, however, target about 60% of the male population. The British Hypertension Society guidelines and new Joint British Societies recommendations achieved the greatest population impact of −27% while maintaining the NNT at 22.2. They did, however, target three quarters of this population. Conclusion: Even effective preventive treatment will have little impact in preventing disease if patients at typical risk are not treated. Whether cholesterol lowering on such a scale should be attempted with drugs raises philosophical, psychological and economic considerations, particularly in view of the high likelihood of individual benefit from statin treatment. More effective nutritional policies to reduce serum cholesterol on a population level and reduce the requirement for statins in primary prevention should also be considered.